STUDY OF SPECIES DIVERSITY OF SPRING FLORA OF PROTECTED AREAS OF MANGISTAU REGION (Eurasian Journal of Ecology, 2025)
The article presents the results of monitoring of the current species composition of higher vascular plants of specially protected natural territories located in the south of Mangistau region - Ustyurt State Nature Reserve and Kenderli-Kayasan state protected area of republican significance. A map of the locations of 2 (out of 5) rare for the region species listed in the Red Data Book of the Republic of Kazakhstan (2014) (Euphorbia sclerocyathium Korov. et Popov, Xylosalsola chiwensis (Popov) Akhani et Roalson (=Salsola chiwensis Popov) and 8 (out of 40) - included in the Catalogue of rare and endangered plant species of Mangistau region (2006) (Salsola arbusculiformis Drob, Ephedra aurantiaca Takht. et Pachom., Zygophyllum turcomanicum Fisch. ex Boiss., Haloxylon aphyllum (Minkw.) Iljin, H. persicum Bunge, Nitraria schoberi L., Capparis herbacea Willd., Tulipa sogdiana Bunge).  Isatis armena L., occurring within the Ustyurt Reserve only in the Kogusem tract, is proposed to be added to the list of rare species of the region, as well as a medicinal species – Ferula foetida (Bunge) Regel, growing in the sands of the Karynzharyk depression of the Kenderli-Kayasan protected area. The list of the Reserve is supplemented with an anthropophilic representative of the family Brassicaceae Burnett. - Olimarabidopsis pumila (Stephan) Al-Shehbaz, O'Kane & R.A. Price (=Arabidopsis pumila (Stephan) N. Busch). The results of analyses of published scientific works on the study of the species composition of the flora of the Ustyurst Reserve by other authors carried out over the last 20 years are also presented. Among other things, the question about the taxonomic volume of the widespread species Phragmites australis (Cav.) Trin. ex Steud. It is suggested that some species of the genus Allium L. grow on the territory of the reserve.Keywords: monitoring, rare species, Ustyurt reserve, Kenderli-Kayasan protected area